2021
DOI: 10.5551/jat.57166
|View full text |Cite
|
Sign up to set email alerts
|

IVUS-Guided Wiring Improves the Clinical Outcomes of Angioplasty for Long Femoropopliteal CTO Compared with the Conventional Intraluminal Approach

Abstract: This study aimed to assess the clinical efficacy of intravascular ultrasound (IVUS)-guided intraplaque wiring for femoropopliteal (FP) chronic total occlusion (CTO).Methods: This single-center, retrospective, observational study was performed at the Japanese Red Cross Kyoto Daini Hospital. From March 2013 to June 2017, a total of 75 consecutive patients (mean age: 75.4 8.5 years; 59 males), who underwent endovascular treatment (EVT), having 82 de novo FP-CTO lesions, were enrolled in this study. Eleven of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…There is no consensus on the optimal guidewire passage route for FP CTO lesions (Soga et al 2013;Mori et al 2017). However, some clinical studies have recently reported that IVUS-guided wiring improves the clinical outcomes of EVT for FP CTO (Mori et al 2017;Tsubakimoto et al 2020). The advantages of intraplaque guidewire crossing are as follows: a stent-less strategy can be realized using a drug-coated balloon even for CTO lesions, it can be expanded reliably and safely even when a stent is implanted, and the antegrade guidewire passage may reduce the need for an extra distal puncture for the retrograde approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no consensus on the optimal guidewire passage route for FP CTO lesions (Soga et al 2013;Mori et al 2017). However, some clinical studies have recently reported that IVUS-guided wiring improves the clinical outcomes of EVT for FP CTO (Mori et al 2017;Tsubakimoto et al 2020). The advantages of intraplaque guidewire crossing are as follows: a stent-less strategy can be realized using a drug-coated balloon even for CTO lesions, it can be expanded reliably and safely even when a stent is implanted, and the antegrade guidewire passage may reduce the need for an extra distal puncture for the retrograde approach.…”
Section: Discussionmentioning
confidence: 99%
“…Various techniques and devices have improved guidewire crossing and initial success for FP chronic total occlusion (CTO) (Kawasaki et al 2008;Urasawa et al 2014;Kitrou et al 2015;Tan et al 2017;Hayakawa et al 2020). Some studies have reported the usefulness of performing an intraluminal approach with intravascular ultrasound (IVUS) guidance (Mori et al 2017;Tsubakimoto et al 2020). Alternatively, IVUSguided intraplaque wiring requires high technical skills, and problems such as procedure time and the number of wires tend to be highlighted.…”
Section: Introductionmentioning
confidence: 99%
“…There is no consensus on the optimal guidewire passage route for FP CTO lesions (Soga et al, 2013, Mori et al, 2017. However, recently, some clinical studies have reported that IVUS-guided wiring improves the clinical outcomes of EVT for FP CTO (Mori et al, 2017;Tsubakimoto et al, 2020). The advantages of intraplaque guidewire crossing are as follows: a stent-less strategy can be realized using a DCB even for CTO lesions, it can be expanded reliably and safely even when a stent is implanted, and the antegrade guidewire passage may reduce the need for an extra distal puncture for the retrograde approach.…”
Section: Discussionmentioning
confidence: 99%
“…Various techniques and devices have improved guidewire crossing and initial success for FP chronic total occlusion (CTO) (Kawasaki et al, 2008;Urasawa et al, 2014;Kitrou et al, 2015;Tan et al, 2017;Hayakawa et al, 2020). Some studies have reported the usefulness of performing an intraluminal approach with intravascular ultrasound (IVUS) guidance (Mori et al, 2017;Tsubakimoto et al, 2020). Alternatively, IVUS-guided intraplaque wiring requires high technical skills, and problems such as procedure time and the number of wires tend to be highlighted.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 On the other hand, recent studies based on IVUS evaluation demonstrated that an intramedial CTO wire passage route was an independent predictor for restenosis after stenting. 3,4 IVUS-guided parallel wiring technique using an IVUS catheter with double rapid exchange lumens has been developed in PCI. 5,6 In general, a conventional IVUS-guided parallel wiring involves 2 separate systems: a first guidewire with an IVUS catheter and a second guidewire with a support catheter.…”
Section: Introductionmentioning
confidence: 99%